Urban cartographies of fear: insecurity and daily life among peripheral residents of the city of La Plata (Delito y Sociedad, 2026)
This research explores the relationship between urban fear and everyday life in the peripheral areas of La Plata (Argentina), specifically in two socioeconomically distinct sectors: Los Hornos and City Bell. Using a qualitative approach based on in-depth interviews and participant observation, the study examines how urban fear reconfigures urban dwelling by shaping perceptions of space, time, and sociability. The findings show that insecurity, far from referring solely to the risk of crime, functions as a symbolic organizer that territorializes fear, alters spatial practices, and reinforces both material and imagined boundaries. It is concluded that urban fear actively contributes to the reproduction of inequalities, consolidating hierarchies and fragmentations in the contemporary city.
Keywords: Urban fear; Insecurity; Urban peripheries; La Plata; Fear; Inequality